2015
DOI: 10.2147/opth.s79723
|View full text |Cite
|
Sign up to set email alerts
|

Visual field changes as an early indicator of glioblastoma multiforme progression: two cases of functional vision changes before MRI detection

Abstract: Glioblastoma multiforme is an aggressive tumor associated with a high rate of recurrence even after maximal therapy. In a disease with poor prognosis and rapid deterioration, early detection of tumor progression is necessary to make timely treatment decisions or to initiate end of life care. We identify two cases where Humphrey visual field testing predated magnetic resonance imaging and positron emission tomography findings of tumor progression by months in glioblastoma multiforme. New or worsening visual fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Loss of RD3 expression correlates with the progression of the pathogenesis in neuroblastoma and a poor survival prognosis [12,14]. Interestingly, rare cases of vision impairment were reported as an early indicator of tumor progression in GBM patients [23,24,25]. Applying a data mining approach, we extended these previous studies by screening and analyzing multi-cohort data sets with respect to RD3 expression.…”
Section: Discussionmentioning
confidence: 92%
“…Loss of RD3 expression correlates with the progression of the pathogenesis in neuroblastoma and a poor survival prognosis [12,14]. Interestingly, rare cases of vision impairment were reported as an early indicator of tumor progression in GBM patients [23,24,25]. Applying a data mining approach, we extended these previous studies by screening and analyzing multi-cohort data sets with respect to RD3 expression.…”
Section: Discussionmentioning
confidence: 92%
“…Peripapillary RNFL thickness reflects neuronal axons, and would allow quantification of ganglion cell axonal loss [ 26 ]. Moreover, VF values estimates functional loss of the whole visual pathway, from retina to cortex [ 27 ]. VF maps show a correspondence with neuronal distribution of RNFL in the ON head, as Garway et al demonstrated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, vision impairment is closely related to glioblastoma. The worsening visual defects are one of Ivyspring International Publisher the important indicator for the investigation of tumor progression in glioblastoma patients [13]. Therefore, due to the coupling and interdependence characteristic of DR complications, the early diagnosis and detection of retinopathy in the diabetic individuals is imperative for the prevention of vision loss in patients.…”
Section: Introductionmentioning
confidence: 99%